EVALUATION OF THE INDONESIAN DOCTOR INTERNSHIP PROGRAM AT BHAYANGKARA TK.III HOSPITAL, PALU CITY - Tobeli, Inggrid; Rivai, Abdul; Nuraisyah, Nuraisyah; Haryono, Dandan (CV. Lafadz Jaya, 2024)
This study aims to evaluate the Indonesian Doctor Internship Program (PIDI) at Bhayangkara Hospital Class III, Palu City. The evaluation was conducted to determine the effectiveness, efficiency, adequacy, equality, responsiveness, and accuracy of this program. The study used a qualitative method with a purposive approach in selecting informants. Data were collected from five main informants, including interns, supervisors, and patients. The results showed that the effectiveness of the internship program was quite good, especially in improving the competence of new doctors in dealing with clinical situations in the field. However, there were shortcomings in the aspects of efficiency and adequacy, especially in terms of time management and distribution of workload among interns. In addition, although the program's responsiveness to patient needs was quite good, improvements were still needed in terms of communication between interns and patients. The aspect of equality or fairness had been running well, where the distribution of tasks and learning opportunities was quite even among interns. The conclusion of this study is that the Indonesian Doctor Internship Program at Bhayangkara Hospital Class III, Palu City has been running quite well, but still requires some improvements in terms of efficiency and adequacy of training.